Determination of Volatile Components in Mountain Tea (Sideritis condensata Boiss. Et. Heldr. Apud Bentham) Grown in its Natural and Agricultural Field Environment - Türkmenoğlu, Güliz; Fakir, Hüseyin (Bartın Üniversitesi, 2023)
In this study, it was aimed to compare the volatile components of Sideritis condensata Boiss. Et. Heldr. Apud Bentham species mountain tea collected from nature and grown under field conditions with HS-SPME GC-MS technique. The cuttings of the plant were collected from Isparta Province, Yenişarbademli District, rocky location of Dedegöl Mountain in April 2020, and were transferred to field conditions at the end of May in the same year after rooted in a greenhouse environment. In June-July 2021, during the flowering period, leaf and flower samples peculiar to the species were collected from both field and natural environments and dried under room conditions. Using solid based micro-extraction technique, 72 volatile components were determined in natural growing environment and 88 volatile components in field envi-ronment in S. condensata by gas chromatography mass spectrometry (GC-MS). Among the volatile com-ponents found in natural habitat and field environment, ?-pinene (9.30%-2.32%), ?-pinene (18.12%-5.66%), ?-ocimene (4.46%-1.06%), trans-caryophyllene (12.77%-0.83%), germacrene-D (10.59%-0.67%), ?-cadinene (2.09%-10.94%), ?-gurjunene (0.03%-16.68%), farnesene (0.98%-6.00%) were identified as the main components of Sideritis condensata. When the volatile components were examined, it was obser-ved that sesquiterpene hydrocarbons were high.

Bu çalışmada doğadan toplanan ve tarla koşullarında yetiştirilen Sideritis condensata Boiss. Et. Heldr. Apud Bentham türü dağ çayının uçucu bileşenlerinin HS-SPME GC-MS tekniği ile karşılaştırılması amaç-lanmıştır. Bitkinin çelikleri Isparta İli, Yenişarbademli İlçesi, Dedegöl Dağı kayalık mevkiinden 2020 yılı Nisan ayında toplanmış ve sera ortamında köklendirilerek aynı yıl Mayıs ayı sonunda tarla koşullarına aktarılmıştır. 2021 yılı Haziran-Temmuz ayında (çiçeklenme dönemi) hem tarla hem de doğal koşullardan türe ait yaprak ve çiçek örnekleri toplanmış ve oda koşullarında kurutulmuştur. Katı faz mikro ekstraksi-yon tekniği kullanılarak, gaz kromatografisi kütle spektrometresi (GC-MS) ile S. condensata 'da doğal yetişme ortamında 72 adet uçucu bileşen ve tarla ortamında 88 adet uçucu bileşen belirlenmiştir. Doğal yetişme ortamı ve tarla ortamındaki uçucu bileşenlerinden ?-pinene (9.30%-2.32%), ?-pinene (18.12%-5.66%), ?-ocimene (4.46%-1.06%), trans-caryophyllene (12.77%-0.83%), germacrene-D (10.59%-0.67%), ?-cadinene (2.09%-10.94%), ?-gurjunene (0.03%-16.68%), farnesene (0.98%-6.00%) Sideritis condensata 'nın ana bileşenleri olarak tespit edilmiştir. Uçucu bileşen sınıflarına bakıldığında seskiterpen hidrokarbon-ların yüksek oranda olduğu bulunduğu görülmüştür.
Dağ Çayı (Sideritis condensata Boiss. Et. Heldr. Apud Bentham) 'ın Doğal ve Tarla Ortamındaki Uçucu Bileşenlerinin Belirlenmesi
. 2021-D1-0132 No
Keywords: Forest Industry Engineering; Orman Endüstri Mühendisliği